International Financial Institutions Ask to Contribute to Climate Protection - G. Ahamer (Финансы: теория и практика, 2021)
The aim of this article is to show in which way international financial institutions (IFIs) can contribute to climate protection projects. The principles of IFIs’ project cycles are explained in the context of the new blending tool. The cooperation with other donors stands in the centre of EU project funding and the notion of leveraging allows to quantify the cooperative effect among different donors. The bulk of this article describes the most relevant IFIs and national development banks with an international focus: Green Climate Fund (GCF), European Investment Bank (EIB), European Bank for Reconstruction and Development (EBRD), French Development Agency (AFD), German Development Bank (KfW), World Bank (WB), Asian Development Bank (ADB), and the Asian Infrastructure Investment Bank (AIIB). For all these IFIs, descriptions are provided and their main fields of actions identified. The procedure of application (the “project cycle”) is illustrated and an overview of their strategies is given. Thus, this article seeks to provide practical guidance on how to cooperate with IFIs and to direct funds into substantially valid and responsible climate projects.